Cognitive Analysis of Hadith on Cleanliness: Cultivating Environmental Awareness in Islamic Religious Education - Baha'udin Arif Minakhur Rohman; Muhid Muhid (STKIP Al Islam Tunas Bangsa dan HEPI, 2026)
This article aims to cognitively analyze the hadiths of the Prophet Muhammad SAW related to cleanliness and their contribution to the formation of environmental awareness in the context of Islamic education. Through a literature study with a qualitative descriptive approach and content analysis, this study identifies the content and meaning of the hadith on cleanliness from a cognitive perspective, highlighting its influence on the thinking process, belief formation, internalization of values, development of executive functions, emotional connections, observational learning, awareness of consequences, attention to detail, social responsibility, empathy, and social consideration. Furthermore, this article explores how the hadiths on cleanliness contribute significantly to fostering environmental awareness through expanding the concept of cleanliness, instilling moral and ethical foundations, encouraging pro-environmental behavior, and emphasizing collective responsibility. Finally, this article proposes various effective cognitive strategies to instill the values ??of cleanliness and environmental awareness in Islamic religious education, including curriculum integration, contextual learning, use of analogies and metaphors, active and participatory learning, behavior modeling, media utilization, and positive reinforcement. It is expected that the implementation of this strategy can internalize the values ??of cleanliness in depth, form sustainable environmental awareness, and encourage real action in preserving nature as a mandate